2021
DOI: 10.3389/fonc.2020.607607
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hedgehog Signaling by miRNAs and Nanoformulations: A Possible Therapeutic Solution for Colorectal Cancer

Abstract: Hedgehog (Hh) signaling aberrations trigger differentiation and proliferation in colorectal cancer (CRC). However, the current approaches which inhibit this vital cellular pathway provoke some side effects. Therefore, it is necessary to look for new therapeutic options. MicroRNAs are small molecules that modulate expression of the target genes and can be utilized as a potential therapeutic option for CRC. On the other hand, nanoformulations have been implemented in the treatment of plethora of diseases. Owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 170 publications
(169 reference statements)
0
6
0
Order By: Relevance
“…Unremitting efforts have been made towards the development of small molecule inhibitors such as SMO antagonists-vismodegib [ 157 ] and cyclopamine [ 158 ], Gli antagonists-GANT61 and GANT58 [ 159 ] and additional PTCH inhibitors to block Hh signaling at various sites in recent years. Yet there have been some serious drawbacks of utilizing these Hh inhibitors for the treatment of cancer, which has been discussed in detail by Javed Z et al [ 160 ]. Hence, designing persistent small molecule inhibitors with excessive bioavailability is still a thorny question.…”
Section: Introductionmentioning
confidence: 99%
“…Unremitting efforts have been made towards the development of small molecule inhibitors such as SMO antagonists-vismodegib [ 157 ] and cyclopamine [ 158 ], Gli antagonists-GANT61 and GANT58 [ 159 ] and additional PTCH inhibitors to block Hh signaling at various sites in recent years. Yet there have been some serious drawbacks of utilizing these Hh inhibitors for the treatment of cancer, which has been discussed in detail by Javed Z et al [ 160 ]. Hence, designing persistent small molecule inhibitors with excessive bioavailability is still a thorny question.…”
Section: Introductionmentioning
confidence: 99%
“…Upon abnormal activation, it leads to cancer at varying organs with its active triggering ability in human CRC. With the current targeting approaches, Hh signaling targeting has been possible, but it has its side effects ( Javed et al, 2021 ). The development and application of new approaches free of side effects is the new challenge in effective human cancer eradicating techniques ( Salaritabar et al, 2019 ).…”
Section: Methods To Knockdown Dclk1mentioning
confidence: 99%
“…In basal cell carcinoma, mutation of the human PTCH1 gene revealed the Hh signaling pathway and its molecular association with malignancy. It was shown that a mutation in PTCH1 gene is accountable for SMO activation leading to abnormal Hh cascade activation and cancer development ( Javed et al, 2021 ). All these genes function as ligands for patched (PTCH1), a 2-pass transmembrane receptor.…”
Section: Methods To Knockdown Dclk1mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of STAT3 signaling pathways (e.g., STX-0119, N4, C188-9, L61H46, or AZD9150) may help in disrupting TC-mediated effects on EMT, potentially inhibiting tumor metastasis and enhancing sensitivity to chemotherapy [ 195 , 196 ]. On the other hand, it should not be forgotten that teratogenicity, immunosuppression, autoimmune reactions, and hematological abnormalities may result from the inhibition of TGFβ or STAT3 [ 199 , 200 ]. Inhibition of TGFβ may additionally result in compromised tissue remodeling, mucosal inflammation, and impaired wound healing [ 199 ].…”
Section: Tuft-cell-based Crc Therapies and Their Considerationsmentioning
confidence: 99%